Ekonomi Halal Perkotaan 5.0: Inovasi Kolaboratif untuk Pengembangan Industri Halal Berkelanjutan di Indonesia: Urban Halal Economy 5.0: Collaborative Innovation for Sustainable Halal Industry Development in Indonesia - Azwar, Azwar; Andi Wawan Mulyawan; Siradjuddin, Siradjuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to formulate the framework of the Urban Halal Economy 5.0 within the context of Tangerang City. This model integrates halal values, sustainability principles, and Society 5.0–based technologies to realize an ethical, prosperous, and sustainable urban environment. In addition, the study seeks to propose a Halal Urban Economy Dashboard as a managerial blueprint that functions not only as a monitoring instrument but also as a collaborative platform connecting the government, business actors, academics, the community, and investors. The research employs a qualitative–descriptive approach through literature review, conceptual analysis, and contextual case studies. Data are obtained from academic literature, policy documents, and global best practices related to the halal economy, smart cities, and the Society 5.0 paradigm. Thematic analysis is used to identify relational patterns among four main pillars: the halal economy, Society 5.0, collaborative innovation, and Islamic urbanism. The findings indicate that the Urban Halal Economy 5.0 offers a model of urban development that is just, inclusive, and sustainable. Meanwhile, the Halal Urban Economy Dashboard is positioned as a strategic instrument to strengthen the integration of data, technology, and multi-stakeholder collaboration. This study highlights the potential of Tangerang City to become a pioneer of the Halal Urban Economy City in Indonesia as well as a global reference point.